HUBUNGAN KEMAMPUAN BERPIKIR KREATIF TERHADAP KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS IV SEKOLAH DASAR NEGERI CIBODAS 5 KOTA TANGERANG - Zhillan Zhalila; Enawar; Dilla Fadhillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to 1) determine the creative thinking ability of class IV-A students of SDN Cibodas 5 Tangerang City in the 2024/2025 academic year, 2) determine the ability to write descriptive essays of class IV-A students of SDN Cibodas 5 Tangerang City in the 2024/2025 academic year, 3) determine the relationship between creative thinking ability and the ability to write descriptive essays of class IV-A students of SDN Cibodas 5 Tangerang City in the 2024/2025 academic year. In order to answer the above questions, this study was designed using a quantitative approach and was conducted at SDN Cibodas 5 Tangerang City. There were 28 students and consisted of 1 class, namely IV-A, which was used as a sample in this study. This sample was taken all because the number was less than 100. This study used a test as an instrument in data collection. Based on data analysis, it was found that 1) the results of the creative thinking ability test with an average score obtained by students reached 87.25, this figure is included in the category of a fairly good level of achievement, 2) the results of the descriptive essay writing ability test with an average score obtained by students reached 88.43, this figure is included in the category of a fairly good level of achievement, thus it can be said that class IV-A students of SDN Cibodas 5 Tangerang City are able to write descriptive essays, 3) the results of the product moment correlation test showed a significance level of 0.00 with a moderate correlation, thus it can be said that the results of the correlation analysis show that there is a relationship between creative thinking and the ability to write descriptive essays in class IV-A students of SDN Cibodas 5 Tangerang City.